2004
DOI: 10.1074/jbc.m310691200
|View full text |Cite
|
Sign up to set email alerts
|

Domain-specific Modification of Heparan Sulfate by Qsulf1 Modulates the Binding of the Bone Morphogenetic Protein Antagonist Noggin

Abstract: We have reported previously that Noggin is a heparinbinding protein and associates with the cell surface through heparan sulfate proteoglycans, where it remains functional for the binding of bone morphogenetic proteins (BMPs). Here we report that the binding of Noggin to the cell surface is highly selective for heparan sulfate and that specific structural features are required for the interaction. Noggin binds most efficiently to heparin sequences composed of 10 or more monosaccharides; N-, 6-O-, and 2-O-sulfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
166
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(173 citation statements)
references
References 31 publications
(36 reference statements)
5
166
1
1
Order By: Relevance
“…We and others showed that both Sulfs are neutral pH endosulfatases, which remove glucosamine-6-O-sulfate from internal glucosamine residues of highly sulfated subregions within heparin/HSPGs (7,9,10). The ability of these enzymes to modulate the heparin/HSPG interactions of a number of growth factors, morphogens, and chemokines has been confirmed in direct binding assays (9,(11)(12)(13).…”
mentioning
confidence: 87%
“…We and others showed that both Sulfs are neutral pH endosulfatases, which remove glucosamine-6-O-sulfate from internal glucosamine residues of highly sulfated subregions within heparin/HSPGs (7,9,10). The ability of these enzymes to modulate the heparin/HSPG interactions of a number of growth factors, morphogens, and chemokines has been confirmed in direct binding assays (9,(11)(12)(13).…”
mentioning
confidence: 87%
“…Total RNAs were extracted using Sepasol I (Nacalai Tesque, Kyoto, Japan) and purified using an RNeasy kit (Qiagen, Hilden, Germany). Total RNAs (5 g) were subjected to reverse-transcription using oligo(dT) [12][13][14][15][16][17][18] and Superscript II (Invitrogen). Quantitative PCR was carried out using a LightCycler and LightCycler FastStart DNA Master SYBR Green I reagent (Roche Diagnostics).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, Sulf1 and Sulf2 are thought to be key regulators of cell proliferation, differentiation, and migration and are also implicated in cancer progression and metastasis (22,23). Biochemical studies have demonstrated that Sulf1 and Sulf2 are most active in the UA2S-GlcNS6S trisulfated disaccharide unit, which is present in the NS domain (9,11,13,16,24,25). In addition, weaker 6-O-desulfation activity is also detectable in the UA-GlcNS6S-disulfated disaccharide unit (11,24,25).…”
mentioning
confidence: 99%
“…Similarly, VEGF binding and activity requires moderately 6-O sulfated HS (Ashikari-Hada et al, 2005;Robinson et al, 2006) and treatment of heparin with human SULF2 abolishes its binding to VEGF (Uchimura et al, 2006). Although the exact nature of the structural HS requirement has not been decoded for BMP4 activity, it has been suggested that strict levels of 6-O sulfation are critical for BMP regulation since in-vitro studies show that exposure to Quail Sulf1 leads to the dissociation of BMP from its inhibitor noggin, allowing BMP to freely associate with its receptor and promote signalling (Viviano et al, 2004).…”
Section: Introductionmentioning
confidence: 99%